Utilization of waste cockle shell (Anadara Granosa) in biodiesel production from palm olein: Optimization using response surface methodology - Boey, Peng-Lim; Maniam, Gaanty Pragas; Abd Hamid, Shafida; Ali, Dafaalla Mohamed Hag (Elsevier Ltd., 2011)
The cockle shell, which is available in abundance, has no any eminent use and is commonly regarded as a waste, was utilized as a source of calcium oxide in catalyzing a transesterification reaction to produce biodiesel (methyl esters). A central composite design (CCD) was used to optimize the two major influential reaction variables: catalyst and methanol amount towards purity and yield of methyl esters. The analysis of variance (ANOVA) indicated that the catalyst has a positive influence on purity but negative on the yield. Meanwhile, the methanol/oil mass ratio showed a positive effect on both purity and yield. Using CCD, the optimum reaction conditions were found to be 4.9 wt.% of catalyst and 0.54:1 methanol/oil mass ratio. The prepared catalyst was capable of being reused under the suggested optimal conditions.